MICROBIAL IMMOBILIZATION OF CADMIUM RELEASED FROM CDO IN THE SOIL - Kurek E.; Bollag J.M. (My University, 2004)
The effect of microorganisms on the fate of Cd introduced into the soil as cadmium oxide (CdO) was investigated. Cadmium oxide (875 µg Cd per gram of soil) was added to γ-irradiated (sterile) and non-sterile soils. The soils were incubated for 90 days at 18 °C under aerobic conditions with moisture kept at 60% of water-holding capacity. Half of the samples in each treatment were supplemented with starch (0.5%, w/w) in order to stimulate microbial growth in the non-sterile soil. After various time intervals (7- or 10-day), soil samples from each treatment were extracted with deionized distilled water (ratio 1:40) or 0.25 M CaCl2 (ratio 1:5). The results indicated that during the incubation period the amount of Cd extracted from the non-sterile soil with either solvent was markedly lower than that extracted from the γ-irradiated sterile control. The addition of starch to the non-sterile soil reduced the concentration of Cd in the 0.25 M CaCl2 extracts without affecting the Cd-content in the water extracts. Short-term experiments in which Cd was added to the soil as a solution of Cd(NO3)2 indicated that irradiation did not affect the sorption of Cd to the soil. The addition of bacterial mass (1 mg of dry weight g-1 soil) decreased the amount of Cd extracted with water as well as that extracted with 0.25 M CaCl2. Under sterile conditions the solubility of CdO in soil extracts was higher than in the other extractants. The addition of glucose (0.5%, w/w) or a glucose/starch mixture (0.5%, w/w of each) to the sterile soil increased the amount of extractable Cd after a short incubation (18 h at 18 °C). The obtained results suggest that primarily physicochemical reactions are involved in dissolving CdO in the soil but that microbial activity may be responsible for the immobilization of the released metal.
Keywords: BACTERIAL MASS; BIOAVAILABLE CD FRACTION